ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL DENGAN MENGGUNAKAN MODEL INDEKS TUNGGAL PADA IDX-30 DI BURSA EFEK INDONESIA - Rachmawati, Eka Nuraini; Azmansyah, Azmansyah; Putri, Eniya Alfinawati; Hanafi, Imam (Journal Competency of Business, 2024)
This study aims to determine which companies are included in the optimal portfolio as well as the proportion of funds from each company that form an optimal portfolio using a single index model. The population in this study were companies included in the IDX-30 index which were listed on the Indonesia Stock Exchange for the period January 2020 - December 2020 and 23 companies that met the criteria to be sampled. The results showed that there were three companies that formed the optimal portfolio, namely PT. Aneka Tambang Tbk (ANTM) with a proportion of 70.32%, PT. United Tractors Tbk (UNTR) with a proportion of 25.85% and the company PT. Indah Kiat Pulp & Paper Tbk (INKP) with a proportion of 3.83%.The expected return on the optimal portfolio that investors will receive is 7.92% and the optimal portfolio risk that investors will bear is 2.57%.